Azobenzene-functionalized iridium(iii) triscyclometalated complexes. Issue 5 (4th September 2014) - Pérez-Miqueo, J.; Telleria, A.; Muñoz-Olasagasti, M.; Altube, A.; García-Lecina, E.; de Cózar, A.; Freixa, Z.
Abstract : Photochromic triscyclometalated iridium(iii ) organometallic complexes based on azobenzene-containing phenylpyridyl-type ligands. Abstract : Twelve Ir(iii ) triscyclometalated compounds containing up to three azobenzene fragments on their structure have been synthesized based on photochromic 2-phenylpyridyl type ligands1–4 . These complexes are intended to study the possibility of transferring the photochromicity of the azobenzene fragment to the organometallic compound, and the effect of the substitution pattern, relative distance of the azobenzene to the metal centre, and number of azobenzenes on their properties.